Yelemat Tirufat: An Overview of the initiative and lessons of experience from selected livestock development interventions in Ethiopia - Dessie, Tadelle; Zewdie, Yihenew; Yilma, Zelalem; Ayalew, Workneh; Haile, Aynalem (International Livestock Research Institute, 2023)
A national consultative Workshop on “Are We Ready for Yelemat Tirufat?”, financed by the International Livestock Research Institute (ILRI) and organised jointly by Ethiopia’s Ministry of Agriculture, ILRI, the International Center for Agricultural Research in the Dry Areas (ICARDA), the International Centre of Insect Physiology and Ecology (icipe) and Land O’Lakes Venture37, was held on 24 and 25 December 2022, in Bahir Dar, Ethiopia.